Pounding between adjacent buildings of varying height coupled through soil - Naserkhaki, Sadegh; El-Rich, Marwan; Abd Aziz, Farah Nora Aznieta; Pourmohammad, Hassan (Techno-Press, 2014)
Pounding between adjacent buildings is a significant challenge in metropolitan areas because buildings of different heights collide during earthquake excitations due to varying dynamic properties and narrow separation gaps. The seismic responses of adjacent buildings of varying height, coupled through soil subjected to earthquake-induced pounding, are evaluated in this paper. The lumped mass model is used to simulate the buildings and soil, while the linear visco-elastic contact force model is used to simulate pounding forces. The results indicate while the taller building is almost unaffected when the shorter building is very short, it suffers more from pounding with increasing height of the shorter building. The shorter building suffers more from the pounding with decreasing height and when its height differs substantially from that of the taller building. The minimum required separation gap to prevent pounding is increased with increasing height of the shorter building until the buildings become almost in-phase. Considering the soil effect; pounding forces are reduced, displacements and story shears are increased after pounding, and also, minimum separation gap required to prevent pounding is increased.